Dialektika Dakwah Minoritas Muslim di Pakuwon City Surabaya - Aziz, Moh. Ali; Subandi, Bambang (Jurnal Komunikasi Islam, 2019)
This article reports on research conducted in 2018 about the dialectic of Muslim minority da'wah in the multicultural-metropolitan community in Pakuwon City Surabaya, using a qualitative descriptive approach. Findings illustrate Muslim minority in Pakuwon City has a strong religious identity and the pleasure of ukhuwah Islamiyah. This is supported by the central role of the commodification agent, namely takmir (mosque committee) of the Al-Madani mosque. In additin, Muslim minority in Pakuwon City makes the Al-Madani mosque a center for da'wah through oral, written, and social movement methods, such as religious sermon, religious forum, web-based media, zakat and qurban, and fundraising for social services. Another finding reveals that the dialectic proselytising of Muslim minority in the multicultural-metropolitan community in Pakuwon City Surabaya produces a symmetrical environmental harmony which is in line with the satisfaction of the da'wah partners.